Enantioselective Dicarbofunctionalization of Unactivated Alkenes by Palladium‐Catalyzed Tandem Heck/Suzuki Coupling Reaction. (5th September 2019) - Zhang, Zhan‐Ming; Xu, Bing; Wu, Lizuo; Wu, Yuanqi; Qian, Yanyan; Zhou, Lujia; Liu, Yu; Zhang, Junliang
Abstract: A highly enantioselective dicarbofunctionalization of unactivated alkenes was implemented by a Pd‐catalyzed asymmetric tandem Heck/Suzuki coupling reaction. This reaction represents the first example of a highly enantioselective intramolecular cyclization/cross‐coupling of olefin‐tethered aryl halides with alkyl‐, alkenyl‐ or arylboronic acids, and provides rapid access to a number of chiral compounds, such as dihydrobenzofurans, indolines, chromanes, and indanes bearing a quaternary stereocenter, in good yields with excellent enantioselectivities. The practicality of this reaction was validated in the modification of biologically complex molecules such as peptides, piperitol, CB2 receptor agonists, etc. Moreover, the synthesis of two enantiomers can be easily realized by simple change in the order of the steps in the coupling sequence. Abstract : Das erste Beispiel einer hoch enantioselektiven intramolekularen Dicarbofunktionalisierung von nicht aktivierten Alkenen mit Alkyl‐, Aryl‐ oder Alkenylboronsäure wird vorgestellt. Es bietet eine effiziente Synthese für chirale benzolkondensierte cyclische Verbindungen mit quartärem Stereozentrum. Ein Enantiomerenpaar konnte synthetisiert werden, indem die Reihenfolge der Schritte in der Reaktionssequenz geändert wurde.